Proteomic Analysis of Rhesus Macaque Brain Explants Treated With Borrelia burgdorferi Identifies Host GAP-43 as a Potential Factor Associated With Lyme Neuroborreliosis - Li, Lianbao; Luo, Lisha; Chen, Taigui; Cao, Wenjing; Xu, Xin; Zhang, Yu; Yue, Peng; Fan, Yuxin; Chen, Jingjing; Liu, Meixiao; Ma, Mingbiao; Tao, Lvyan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Lyme neuroborreliosis (LNB) is one of the most dangerous manifestations of Lyme disease, but the pathogenesis and inflammatory mechanisms are not fully understood. Methods: Cultured explants from the frontal cortex of rhesus monkey brain (n=3) were treated with live Borrelia burgdorferi (Bb) or phosphate-buffered saline (PBS) for 6, 12, and 24 h. Total protein was collected for sequencing and bioinformatics analysis. Changes in protein expression in the explants over time following Bb infection were screened. Results: We identified 1237 differentially expressed proteins (DEPs; fold change ≥1.5 or ≤0.67, P-value ≤0.05). One of these, growth-associated protein 43 (GAP-43), was highly expressed at all time points in the explants. The results of the protein-protein interaction network analysis of DEPs suggested that GAP-43 plays a role in the neuroinflammation associated with LNB. In HMC3 cells incubated with live Bb or PBS for 6, 12, and 24 h, real-time PCR and western blot analyses confirmed the upregulation of GAP-43 mRNA and protein, respectively. Conclusions: Elevated GAP-43 expression is a potential marker for LNB that may be useful for diagnosis or treatment.